Modular synthesis of N-glycans and arrays for the hetero-ligand binding analysis of HIV antibodies - Shivatare, Sachin S.; Chang, Shih-Huang; Tsai, Tsung-I; Tseng, Susan Yu; Shivatare, Vidya S.; Lin, Yih-Shyan; Cheng, Yang-Yu; Ren, Chien-Tai; Lee, Chang-Chun David; Pawar, Sujeet; Tsai, Charng-Sheng; Shih, Hao-Wei; et al. (Nature chemistry, 2016)
A new class of broadly neutralizing antibodies (bNAbs) from HIV donors has been reported to target the glycans on gp120—a glycoprotein found on the surface of the virus envelope—thus renewing hope of developing carbohydrate-based HIV vaccines. However, the version of gp120 used in previous studies was not from human T cells and so the glycosylation pattern could be somewhat different to that found in the native system. Moreover, some antibodies recognized two different glycans simultaneously and this cannot be detected with the commonly used glycan microarrays on glass slides. Here, we have developed a glycan microarray on an aluminium-oxide-coated glass slide containing a diverse set of glycans, including homo- and mixed N -glycans (high-mannose, hybrid and complex types) that were prepared by modular chemo-enzymatic methods to detect the presence of hetero-glycan binding behaviours. This new approach allows rapid screening and identification of optimal glycans recognized by neutralizing antibodies, and could speed up the development of HIV-1 vaccines targeting cell surface glycans. The glycoprotein gp120 is found on the surface of the HIV viron; it is essential for virus entry into cells. Now, an efficient modular synthesis of N -glycans and the preparation of a mixed-glycan array on aluminium-oxide-coated glass slide is described. This is a vital step in understanding the complex compositions of gp120 and thus important for the development of new HIV therapies.